USE OF RENEWABLE ENERGY IN RURAL AREAS: LITERATURE REVIEW AND APPLICATION IN COMMUNITY SERVICE - Melyana R Pugu; Loso Judijanto; Joni Bungai (Adiba Aisha Amira, 2023)
This study aims to explore the potential and implementation of renewable energy in rural areas as an effort to support sustainable development and improve people's quality of life. Using the literature research method, this study collected and analyzed data from various sources in accordance with the research context. The results show that the implementation of renewable energy in rural areas has significant positive impacts on the local economy, education, and environmental awareness of the community. It was also found that the active participation of communities in the decision-making process, planning and implementation of renewable energy projects plays an important role in improving project sustainability and success. The research underscores the need for a more inclusive approach to the planning and execution of energy projects, where community education and empowerment are key. Finally, this research offers insights into how renewable energy projects can serve as a means of community service, establish communal cooperation, and serve as a model for future similar initiatives in other rural areas.